Innovation and Marketing Strategy for Nggoli Cloth Products in Monta Baru Village, Lambu District, Bima Regency - hendra, hendra; Muhamadong, Muhamadong; Ardiansyah, Nike; Iptidaiyah, Muhamad; Lutfi, Muhamad; Junaidin, Junaidin; Irfan, M (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Lambu District in Bima Regency, with an area of 9.91 km², is the center of micro-industrial development, including Nggoli woven fabric craftsmen and shallot farming. Although this superior product has development potential, craftsmen still face various problems such as weak business management, limited marketing, and low utilization of technology. The study identified that artisans experienced limitations in financial management, the use of internet technology, and managerial innovation, as well as problems in brand registration. This community service program aims to overcome these problems through business management and e-marketing coaching. The methods used include participatory, cognitive, affective, and skills approaches, as well as the stages of preparation, investigation, transformation, incubation, verification, implementation, evaluation, and development. The collaboration between the Community Service Team of Mbojo Bima University, Nggoli fabric craftsmen, and the Bima Regency SME Trade and Industry Office resulted in an improvement in business management and e-marketing capabilities. The results of this program show that artisans now better understand financial management and product pricing strategies, as well as utilize digital technology to market products more widely. Support from local governments and active involvement of partners in the workshop have strengthened the success of the program. With a new understanding in digital management and marketing, it is hoped that artisans can be more independent and successful in developing their businesses.